2021
DOI: 10.1186/s12879-021-06100-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying risk factors for late HIV diagnosis and survival analysis of people living with HIV/AIDS in Iran (1987–2016)

Abstract: Background Late-diagnosis of HIV is a major challenge for the control and prevention of AIDS in the world. The present study aimed to specify factors associated with the late diagnosis of HIV in Iran from 1987 to 2016. Methods In this retrospective cohort study, data for 4402 diagnosed HIV/AIDS patients were extracted from 158 behavioral disease counseling centers of 31 Iranian provinces. We defined late diagnosis as having a CD4 count less than 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
2
19
1
1
Order By: Relevance
“…The prevalence is higher than the reported figure from China (40.1%) and lower than in Senegal (71%) [ 11 , 20 ]. Diagnosis of HIV in Iran has clearly less quality than the goals defined by UNAIDS, which leads to the loss of opportunities for early diagnosis and treatment, and therefore diagnosing patients in the advanced stage with a poor prognosis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence is higher than the reported figure from China (40.1%) and lower than in Senegal (71%) [ 11 , 20 ]. Diagnosis of HIV in Iran has clearly less quality than the goals defined by UNAIDS, which leads to the loss of opportunities for early diagnosis and treatment, and therefore diagnosing patients in the advanced stage with a poor prognosis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Iran has the largest concentrated HIV epidemic among the Middle East countries (12). According to the latest report (2020) from UNAIDS, about 54,000 Iranians are living with HIV and 3,200 PLHIV are dying of AIDS-related illnesses annually.…”
Section: Introductionmentioning
confidence: 99%
“…According to this report, the most common way of HIV transmission in Iran is drug injection, and most cases occur in men of 15-44 years of age. Also, only 42% of PLHIV in Iran are aware of their disease status, and only 29% receive ART (12,13). Despite the importance of HIV and its timely treatment initiation, we found no published information on the rate of late ART initiation among PLHIV in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, high percentages of late presentation were shown over the time, with more than half each year. It is higher than that in some countries of Europe ( 14 , 19 22 ), Australia ( 17 ), and the United States ( 23 ), lower than that in Panama ( 18 ), South Africa ( 24 , 25 ), Ethiopia ( 26 ), and Guangxi of China ( 12 ), and similar to that in Iran ( 27 ). It is important to notice that higher percentages of late presentation were indicated among people over 40 years old, retirees, farmers, married, heterosexuals, and people registered in Suzhou in our study.…”
Section: Discussionmentioning
confidence: 72%